LXR promotes the maximal egress of monocyte-derived cells from mouse aortic plaques during atherosclerosis regression - Feig, Jonathan E.; Pineda-Torra, Ines; Sanson, Marie; Bradley, Michelle N.; Vengrenyuk, Yuliya; Bogunovic, Dusan; Gautier, Emmanuel L.; Rubinstein, Daniel; Hong, Cynthia; Liu, Jianhua; Wu, Chaowei; van Rooijen, Nico; et al. (The Journal of Clinical Investigation, 2010)
We have previously shown that mouse atherosclerosis regression involves monocyte-derived (CD68+) cell emigration from plaques and is dependent on the chemokine receptor CCR7. Concurrent with regression, mRNA levels of the gene encoding LXRα are increased in plaque CD68+ cells, suggestive of a functional relationship between LXR and CCR7. To extend these results, atherosclerotic Apoe–/– mice sufficient or deficient in CCR7 were treated with an LXR agonist, resulting in a CCR7-dependent decrease in plaque CD68+ cells. To test the requirement for LXR for CCR7-dependent regression, we transplanted aortic arches from atherosclerotic Apoe–/– mice, or from Apoe–/– mice with BM deficiency of LXRα or LXRβ, into WT recipients. Plaques from both LXRα- and LXRβ-deficient Apoe–/– mice exhibited impaired regression. In addition, the CD68+ cells displayed reduced emigration and CCR7 expression. Using an immature DC line, we found that LXR agonist treatment increased Ccr7 mRNA levels. This increase was blunted when LXRα and LXRβ levels were reduced by siRNAs. Moreover, LXR agonist treatment of primary human immature DCs resulted in functionally significant upregulation of CCR7. We conclude that LXR is required for maximal effects on plaque CD68+ cell expression of CCR7 and monocyte-derived cell egress during atherosclerosis regression in mice.